SOCIAL, CULTURAL AND HEALTH DETERMINANTS AND RISK FACTORS IN ADOLESCENT PREGNANCY IN POOR AND DEVELOPING COUNTRIES - Legawati, Legawati; Nugraheni, Sri Achadi (JOURNAL OF RESEARCH IN PUBLIC HEALTH SCIENCES, 2019)
Teenage pregnancy is one of the important problems in the 21st century. There are more than 14 million teenagers who have given birth every year. There are 12.8 million occurrences in developing countries. The highest level in Africa. There are several other highest countries, including India, Bangladesh, Latin America and the Caribbean. The birthrate per 1000 at the age of 15-19 years is 115 in Aprika, 75 in Latin America and the Caribbean and 39 in Asia. This review aims to identify health determinants and risk factors for adolescent pregnancy. This study uses framewotk from Arskey and O?malley. The search engines used are PubMed, Medline, Science Direct, EBSCO, Cambridge Core, Proquest, Emerald insight, Scopus, Spinger. Online search engines get a number of 7257 relevant for citation which 367 qualify after a title and abstract review. After screening through a full text review article, a total of 20 articles that met the inclusion criteria were obtained. Teenage pregnancy is influenced by many factors including poverty, socio-economic and culture, norms and beliefs, low education (adolescents and parents), dropping out or being expelled from school so that it influences the opportunity to follow continuing education, adolescent self-esteem, closeness to family especially mothers , the presence of fathers and family structures and family acceptance of adolescent risk behavior. Given the condition of teenage pregnancies that are still high and have many negative impacts on maternal and infant health, a team is needed to establish a health system that is oriented to adolescent health, especially for teenage pregnancy, which should have been prevented beforehand. If, finding a teenage pregnant woman, it is expected that the health condition of the mother and baby will be more optimal.